Medieval Chinese society and the local "community" - Tanigawa, Michio, 1925-2013.; Fogel, Joshua A., 1950- (Berkeley, Calif. : University of California Press, 1985)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1985.
Chinese society and feudalism: An investigation of the past literature -- Introduction -- Chinese historical studies in the postwar period and the development of the conceptions of feudalism -- The evolution of critiques of theories of unilinear development and the problem of feudalism -- Concluding remarks -- The medieval period in China: Society in the six dynasties and Sui-T'ang periods and the "community" -- Transcending the world of antiquity -- The medieval "community" and aristocratic society.
Translation of: Chūgoku chūsei shakai to kyōdōtai.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: China -- Social conditions -- 221 B.C.-960 A.D.; Social history -- Medieval, 500-1500.; Chine -- Conditions sociales -- 221 av. J.-C.-960.; Histoire sociale -- 500-1500 (Moyen Âge); POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; HISTORY / Asia / China; Social conditions; Social history -- Medieval; China; Chine -- Conditions sociales -- 221 av. J.-C.-960.; 221 B.C.-1500 A.D